(3fjd GdeQGO aj CMhGd GdYQGb hHZOGOs - (3YHGS Hf LhGO Hf QLH Hf YHO Gddg GdHZOGOj GdTGaYj,J (B1333 (3g` s
(3ChdgG (B:s
(3CeG HYO , agPg fHPI jSjQI JJYdb HPcQ CMhGd GdYQGb, ef GdbQi hGdHdGO , dGSjeG Yjf bdGOJI HZOGO s
(3BNQgG (B:s
(3fLR hGdMeO ddg JShjO gPG GdeNJUQ Hbde eDdag YGe KdGK hKdGKjf hKdGKeGFI hCda s
(3hYdjgG Cf GdeDda CYGO GdfXQ ajgs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B259s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B465 s
Keywords: (3GdJGQjNs